Artistic Functions of Distorted Speech in the “Fandorin corpus” by B. Akunin - A. B. Borunov (Научный диалог)
The speech characteristics of the characters of Boris Akunin’s “Fandorin corpus” as a cycleforming principle are analyzed. Attention is paid to distorted speech, analyzed in terms of language levels. The results of a comparative analysis of the speech characteristics of four characters, in whose speech there are examples of distortion, are presented. The question is raised about the status of the language they speak: in fact, despite the external similarity of their speech, the structural principles of distortion are significantly different. Attention is paid to such types of distortions as phonetic, lexical, grammatical. A classification of speech distortions characteristic of characters from Akunin’s works is proposed. The novelty of the research is seen in the fact that the speech characteristics of the characters are considered in the light of the structuralist concept of the levels of the language system and serves as a key to identifying the criminal in those works in which the author does not reveal his name to the reader until the last lines. The analysis of speech strategies of the characters is carried out. The relevance of the study is due to the identification of the cyclical role of these strategies in the plot of the works included in the “Fandorin corpus”. Various distortion strategies have been proven to be used as a postmodern game with the reader and represent the key to understanding the essence of the character. Key words: